2018
DOI: 10.1111/jnu.12390
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Nursing Work Environment and Health‐Promoting Behaviors of Nurses and Nursing Performance Quality: A Multilevel Modeling Approach

Abstract: Organizational efforts to provide sufficient staffing and resources, boost the development of personal resources among nurses, and promote nurses' responsibility for their own health could be effective strategies for improving nursing performance quality and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 40 publications
4
84
0
8
Order By: Relevance
“…In Cho and Han's study (), of the 510 survey questionnaires that were distributed to 66 wards in five hospitals, a total of 487 surveys were returned. Among the collected surveys, data from 441 were analysed, excluding 10 missing copies and 36 copies that comprised nurse managers' responses.…”
Section: Methodsmentioning
confidence: 99%
“…In Cho and Han's study (), of the 510 survey questionnaires that were distributed to 66 wards in five hospitals, a total of 487 surveys were returned. Among the collected surveys, data from 441 were analysed, excluding 10 missing copies and 36 copies that comprised nurse managers' responses.…”
Section: Methodsmentioning
confidence: 99%
“…This study used a cross‐sectional design and employed data from the nurses health and nursing performance (NHNP) study, collected from March and May 2016 (Cho & Han, ). Briefly, 487 nurses at five hospitals (two teaching hospitals and three non‐teaching hospitals) in South Korea participated in the NHNP study (return rate, 95%).…”
Section: The Studymentioning
confidence: 99%
“…A study focusing on hospital nurses in Japan likewise found that quality of the nursing practice environment was a significant predictor of quality of patient care (Anzai, Douglas, & Bonner, ). A study conducted in South Korea (Cho & Han, ) found that nurses who perceived that their hospitals had sufficient resources and staffing also perceived their nursing performance quality as better. Positive correlations have been consistently found between quality of the practice environment and patient safety in Europe, the US, and Asia.…”
mentioning
confidence: 99%